Formaldehyde column density measurements as a suitable pathway to estimate near‐surface ozone tendencies from space. Issue 21 (8th November 2016) - Schroeder, Jason R.; Crawford, James H.; Fried, Alan; Walega, James; Weinheimer, Andrew; Wisthaler, Armin; Müller, Markus; Mikoviny, Tomas; Chen, Gao; Shook, Michael; Blake, Donald R.; Diskin, Glenn; et al.
Abstract: In support of future satellite missions that aim to address the current shortcomings in measuring air quality from space, NASA's Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER‐AQ) field campaign was designed to enable exploration of relationships between column measurements of trace species relevant to air quality at high spatial and temporal resolution. In the DISCOVER‐AQ data set, a modest correlation ( r 2  = 0.45) between ozone (O3 ) and formaldehyde (CH2 O) column densities was observed. Further analysis revealed regional variability in the O3 ‐CH2 O relationship, with Maryland having a strong relationship when data were viewed temporally and Houston having a strong relationship when data were viewed spatially. These differences in regional behavior are attributed to differences in volatile organic compound (VOC) emissions. In Maryland, biogenic VOCs were responsible for ~28% of CH2 O formation within the boundary layer column, causing CH2 O to, in general, increase monotonically throughout the day. In Houston, persistent anthropogenic emissions dominated the local hydrocarbon environment, and no discernable diurnal trend in CH2 O was observed. Box model simulations suggested that ambient CH2 O mixing ratios have a weak diurnal trend (±20% throughout the day) due to photochemical effects, and that larger diurnal trends are associated with changes in hydrocarbon precursors. Finally, mathematical relationships were developed from first principles and were able to replicate the different behaviors seen in Maryland and Houston. While studies would be necessary to validate these results and determine the regional applicability of the O3 ‐CH2 O relationship, the results presented here provide compelling insight into the ability of future satellite missions to aid in monitoring near‐surface air quality. Key Points: A correlation between column CH2 O and near‐surface O3 measurements was observed and could be useful for monitoring air quality from space The strength of the correlation between column CH2 O and near‐surface O3 is highest when there is temporal variability in CH2 O The O3 ‐CH2 O relationship appears to be strongest in regions where emissions of biogenic VOCs dominate the local hydrocarbon mix